(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1992)
The Holocene sedimentary filling in the estuaries of the Cantabrian Coast has been studied by the boreholes EL1, Ria of Bilbao, and IS2, Ria of Bidasoa. The micropalaeontological analysis of both litoral sequences has allowed to recognize 5 and 7 different benthic foraminifera assemblages respectively. These have been used to determine the correspondant estuarine depositional subenvironments (from subtidal to middle/upper marsh). Two recurrent phases of sediment build up as sea level rose were distinguished. They were interpreted as the consequence of two different marine advances on this region: a first one dared around 8000 years B.P. (Atlantic stage) and a second one identified around 2500 years B.P. (Subatlantic srage).